Family Legacy of Diabetes-Related Behaviors: An Exploration of the Experiences of African American Parents and Adult Children. (May 2019) - Routh, Brianna; Hurt, Tera; Winham, Donna; Lanningham-Foster, Lorraine
African Americans are at higher risk of developing type 2 diabetes mellitus (T2DM), and this risk may be influenced by familial experiences and cultural norms throughout the life course. This led us to conduct this study of 20 African American families with strong histories of T2DM to explore familial complexities that prevent or help manage diabetic symptoms. Experiences were analyzed inductively through individual family profiles created using content-analytic summaries. When profiles were further analyzed for emerging and theoretically informed data patterns, two themes emerged: (a) family interactions characterized by T2DM-related actions and communication patterns, and (b) intergenerational patterns of openness characterized by variations in approach within generational cohort and parental gender. Through inquiries related to intergenerational experiences with T2DM, nursing and health care professionals may be better able to tailor and promote success for prevention and management of behaviors among high-risk African Americans.